Fetal Triploidy Syndrome: a case report from Global Reference Laboratory, Mumbai, India - Pande, Shailesh; Choubal, Nitin; Parulekar, Ashish; Pais, Anurita; Chheda, Pratiksha; Salunkhe, Yogita; Matkar, Sunmeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Triploidy is a complete extra set of chromosomes. In the current case report, we present the case of a 29-year-old pregnant female who was referred to Department of Genetics, Metropolis Healthcare Ltd, Mumbai. Real-time sonography of the gravid uterus was done using a 3C RS multi-frequency probe. Placenta was observed to be posterior. The findings were suggestive of a single viable foetus with an average gestational age of 14.6 weeks at 14-15 weeks of pregnancy and only mild placental thickening at 17-18 weeks of pregnancy was detected on Ultrasound at the time of Amniocentesis. The fetal chromosomal study on amniotic fluid by Fluoroscence insitu hybridization (FISH) revealed trisomy status for chromosome 13, 18, 21, X and Y in 100% of the cells analysed and the fetal karyotype revealed a presence of extra set of chromosomes (69) in all the analysed cells. Parental blood karyotype was done for checking cytogenetic abnormality or variations. FISH studies with POC specimen revealed Trisomy status for chromosomes 13, 18, 21 and presence of extra Sex chromosome (XXY) in all cells analysed.